Study Of Reliability Of Over Current Relay (OCR) On Power Transformer Based On Matrix Laboratory - Ryan Rivaldi Simatupang; Solly Aryza; Hamdani (Sean Institute, 2021)
Distribution of electrical energy by There are many aspects that need to be considered, one of which is the reliability of the protection system. The protection system is a system that functions to prevent or limit damage to equipment due to interference and in the distribution of the electric power system cannot be separated from interference, therefore a protection is needed so that electrical energy can be channeled to consumers properly, where the types of protection include: overcurrent relay. This study describes an overcurrent detector that exceeds a predetermined setting value, whether caused by a short circuit between phases or an overload, from the calculation of the interphase fault current that occurs, the largest value of the short circuit fault current between phases is located at the 0% point. of 8113.79 Ampere and the smallest value of short-circuit fault current between phases is located at the 100% point of 1208.10 Ampere and comparison with experiments using the Matrix Laboratory (MATLAB) application obtained results that are not too far from the results of manual calculations.